Dietary Protein Requirement for Optimising Growth Responses of Asian Cichlid, Etroplus suratensis (Bloch) - V., Jayaprakas; S., Sunil Kumar (Fishery Technology, 2025)
Supplementary diets having three levels of protein viz., 30, 35 and 40% were fed to E. suratensis for a period of 120 days. Growth, feed conversion efficiency, digestive enzyme activity, nucleic acid content and carcass proximate composition were evaluated. Highly significant (p<0.01) superior growth was obtained with 35% protein diet. High feed conversion efficiency, protein efficiency ratio (PER) and good digestibility of protein, fat and carbohydrate were obtained with the diet containing 35% protein. RNA/DNA ratio in the muscle was maximum in this group, followed by the 30% and 40% protein groups. High protein content was noticed in the carcass of fish fed on 35% protein-diet.